Perbaikan Fasilitas Kerja Area Finishing dengan Pendekatan Lean dan Metode MOST guna Meningkatkan Produktivitas PT. XYZ - Prasetyo, Andiko; Puspanantasari Putri, Erni (Innovative: Journal Of Social Science Research, 2024)
XYZ is a company that produces paper products including the spiral division. The spiral finishing area has wasteful work areas including transportation waste, and movements that result in a lack of focus on work. The methods used are VSM, Nordic Body Map and MOST calculations. The results of processing data on the spiral division of the finishing section with an average book revision work per person produce one book revision unit taking a standard time of 60.23 seconds/pcs and in 7 working hours producing 1720 books for 4 operators, while after improving the work system with the proposed shelf design and placement as minimal as possible in the finishing area, the results were obtained for three revision operators 22.46 seconds/pcs revision, per person and one person for wire button work and quality check 15.41 seconds and in 7 working hours produces 2562 book revisions for 4 operators.